Mycobacterium Tuberculosis and Mycobacterium Leprae Co-infection: A Case Report - Bimal K Agrawal (Journal of Clinical and Diagnostic Research, 2019)
Tuberculosis (TB) is one of the oldest diseases known to affect man caused by bacteria of the Mycobacterium tuberculosis complex. World Health Organisation (WHO) estimate shows that 10.4 million new cases of tuberculosis occurred worldwide in 2016. Likewise, leprosy is another age-old disease caused by Mycobacterium leprae. Leprosy is predominantly a disease seen in the developing world with a worldwide estimation of 0.6 to 8 million affected individuals. Both are chronic diseases, prevalent in various parts of the world and account for significant disease morbidity. Co-infection of the two Mycobacteria, although rare, has been reported to occur. Here the present authors discuss one such case of co-infection with both Mycobacteriae. A 24-year-old male was presented with fever, cutaneous lesion and cough. The clinical diagnosis of leprosy was made and chest X-ray was suggestive of tuberculosis. After confirming the diagnosis, the patient was treated with four antitubercular drugs as per the guidelines along with dapsone and clofazimine. The patient gradually improved and after six months treatment was continued only for leprosy.